The Influence of Corporate Governance, Profitability, and Company Size on Environmental Disclosure (A Study of Mining Companies Listed on the Indonesian Stock Exchange (IDX) for the 2021-2024 Period) - Andini Anissa; M. Muhayin A. Sidik; Lihan Rini Puspo Wijaya (Jurnal Pengabdian Nusantara, 2026)
This study aims to analyze the influence of corporate governance (committee, audit, independent board of commissioners, and board of commissioners), profitability (ROA and ROE), and company size on environmental disclosure in 31 mining companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period. Using multiple linear regression with data from annual reports and sustainability reports based on the 2021 GRI Standards, this study found that audit committees, independent board of commissioners, and board of commissioners significantly influence the level of environmental disclosure, while ROA, ROE, and company size did not show a significant influence. These findings indicate that corporate governance is a greater determinant of environmental information disclosure than profitability or company scale, and emphasize the importance of oversight and accountability in encouraging more transparent environmental disclosure practices.